ANALISA KEBUTUHAN TENAGA KEPERAWATAN (Studi Kasus di Puskesmas Kebonagung) - Tri Suwarto; Muhammad Purnomo; Sri Siska Mardiana (Universitas Ngudi Waluyo, 2021)
Nursing services is an integral part of medical services system, 60% of wokers at public health center (Pukesmas)are nurses and therefore the plan of nurses, especially in determining the number of personnel, should be well-considered in order to obtain effective and efficient staff so that number of woker fits the requiref standard.The objective of this research is yo find out the need for nurses based on the analysis of need for nurses inside and outside the building of Puskesmas Kebonagung Kabupaten DemakThis research is adescriptive case study using cross-sectional framework. This research was done in a week at Puskesmas Kebonagung with atotal sample of seven nurses. The method used in data collecting was distributing from of working list systematically to nurses at Puskesmas Kebonagung .The result of this research showed thed the working time used up by nurse for activities inside the building: productive time compared to non-productive time is 66.14% : 33.86 %. Working time outside the building of Puskesmas Kebonagung for Program Perkesmas took productive time compared to non-productive time of 66.96% : 24.40%; Program P2M took that of 81.83% : 18.17%; Program PKM took that of 73.34% : 26.66%; and program UKS had tis ratio of 78.60% : 21.40%.With an effective nursing time of 3.22 hours per patient per day, it will need 16 nursing wokers according to formula from Depkes (2002),according to Swansbrug (1996) it will need 14 workers,and from Hasibuan (2003) 13 workers are needed. This result showed that the number of needed nurses at Puskesmas Kebonagung should be uncreased. New 6 – 9 staff should be added to the previous nurses.